2012
DOI: 10.1002/yea.2903
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol induces antioxidant defence via transcription factor Yap1p

Abstract: Resveratrol is a polyphenol suggested to play a protective role against ageing and agerelated diseases. We demonstrate that administering low-doses of resveratrol causes ROS accumulation and transcriptional changes in yeast cells and human adipocytes. These changes in gene expression depend on the oxidative transcription factor Yap1p. In particular, resveratrol induces expression of Yap1p gene targets, such as TRX2, TRR1 or AHP1, in a Yap1p-dependent mode. Under resveratrol treatment, Yap1p is phosphorylated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 34 publications
(41 reference statements)
4
23
0
Order By: Relevance
“…Thus, the negative-oxygen consumption values reported in the present study could be associated with an increase in O 2 concentration in the medium as a result of the reactions by superoxide dismutase on O 2 .-(McCord and Fridovich 1969) and subsequent activity of catalase on H 2 O 2 (George 1947). In agreement with this observation, has been reported that RSV acts as a pro-oxidant molecule in S. cerevisiae (Escote et al 2012). Altogether, these findings support the hypothesis that RSV inhibits respiration generating a negative energy status of the cell with a subsequent stimulation of glycolysis to compensate the energy state.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the negative-oxygen consumption values reported in the present study could be associated with an increase in O 2 concentration in the medium as a result of the reactions by superoxide dismutase on O 2 .-(McCord and Fridovich 1969) and subsequent activity of catalase on H 2 O 2 (George 1947). In agreement with this observation, has been reported that RSV acts as a pro-oxidant molecule in S. cerevisiae (Escote et al 2012). Altogether, these findings support the hypothesis that RSV inhibits respiration generating a negative energy status of the cell with a subsequent stimulation of glycolysis to compensate the energy state.…”
Section: Discussionsupporting
confidence: 91%
“…This increase in ROS following resveratrol treatment has been seen previously in yeast cells 24 , human adipocytes 24 , and cancer cell-lines 25 . In addition, the increase in ROS following preconditioning treatments is a well observed phenomenon, and inhibition of ROS production has been shown to ameliorate preconditioning-induced neuroprotective effects 26 .…”
Section: Discussionsupporting
confidence: 81%
“…The effect of MEL on S. cerevisiae may also be comparable to the effect of resveratrol on yeast (Escoté et al, 2012), which induces Yap1p activity (the major regulator of genes involved in the oxidative stress response) to reduce ROS levels under oxidative stress.…”
Section: Discussionmentioning
confidence: 99%